El tratamiento de Datos Personales y su Regulación Normativa en el Ecuador según las Nuevas Tecnologías de la Información y la Comunicación. - Pardo Guamán, Lady Carolina (2023)
Please, distinguished reader, to delve into this investigative work entitled: "THE TREATMENT OF PERSONAL DATA AND ITS REGULATION IN ECUADOR ACCORDING TO THE NEW INFORMATION TECHNOLOGIES AND THE COMMUNITY" The purpose of this research work is to analyze the challenges generated by the application of the Organic Law for the Protection of Personal Data in Ecuadorian private sector companies that treatment personal data, since the law establishes obligations for companies in their role as data controllers, which must implement a series of internal measures that contribute to an adequate protection of citizens' personal data; For this purpose, the law establishes a period of two years for those responsible to adapt to the precepts established within the provisions, before the sanctioning regime begins to apply; however, the time established by the legislator is insufficient. For this purpose, a qualitative approach methodology was applied, and as a data collection instrument, experts in the field of personal data protection were interviewed to know their opinion about the challenges generated by the implementation of the law in the internal processes of the companies, with the purpose of proposing reforms to the transitory provisions of the Organic Law for the Protection of Personal Data.